Incidence of acute aortic dissections in patients with out of hospital cardiac arrest : a systematic review and metaanalysis of observational studies - Machado, Carolina Maria Gonçalves (2022)
Trabalho Final do Curso de Mestrado Integrado em Medicina, Faculdade de Medicina, Universidade de Lisboa, 2021